Doświadczenia w stosowaniu multimedialnego programu nauczania interkulturowej komunikacji w biznesie na przykładzie projektu COM-IN-EUROPE - Śliwa, Anna (Experience in Using a Multimedia Program for Teaching Intercultural Communication in Business on the Example of COM-IN-EUROPE Project, 2008)
The COM-IN-EUROPE programme was created for the development of communication skills of technical managerial staff, for engineers and employees responsible for regular contacts with foreign partners. As an interactive multimedia programme it is designed primarily for self-study. Applying it for regular classes with students was a challenge both for the teacher and for the students. The paper discusses both the problems resulting from using this method and its measurable benefits, as well as the level of students' satisfaction determined in a survey.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 141-148